De kop van de stoet. V.l.n.r.: Kuiler, ?, ?, de Vries, ?, Drees, Albarda, ?, ?. Uit: coll. Diepenhorst, album 27
De kop van de stoet. V.l.n.r.: Kuiler, ?, ?, de Vries, ?, Drees, Albarda, ?, ?. Uit: coll. Diepenhorst, album 27.